2003
DOI: 10.1063/1.1604962
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid silicon–organic nanoparticle memory device

Abstract: We demonstrate a nonvolatile electrically erasable programmable read-only memory device using gold nanoparticles as charge storage elements deposited at room temperature by chemical processing. The nanoparticles are deposited over a thermal silicon dioxide layer that insulates them from the device silicon channel. An organic insulator deposited by the Langmuir–Blodget technique at room temperature separates the aluminum gate electrode from the nanoparticles. The device exhibits significant threshold voltage sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 23 publications
0
72
1
Order By: Relevance
“…Polymer memory devices may be able to fulfil the criteria highlighted in the aforementioned papers, and so far there have been demonstrations of devices based on metal nanocluster layers by Ma et al (2003), Bozano et al (2004) and Tondelier et al (2004). The use of gold nanoparticles (encapsulated in organic ligands) in hybrid organic/inorganic memory devices has been demonstrated by Paul et al (2003) and Kolliopoulou et al (2003). Möller et al (2003) showed that the combination of organic materials and silicon diodes can be used to produce a write-once read-many-times (WORM) memory device.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer memory devices may be able to fulfil the criteria highlighted in the aforementioned papers, and so far there have been demonstrations of devices based on metal nanocluster layers by Ma et al (2003), Bozano et al (2004) and Tondelier et al (2004). The use of gold nanoparticles (encapsulated in organic ligands) in hybrid organic/inorganic memory devices has been demonstrated by Paul et al (2003) and Kolliopoulou et al (2003). Möller et al (2003) showed that the combination of organic materials and silicon diodes can be used to produce a write-once read-many-times (WORM) memory device.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the fabrication processes described in the MOS capacitor-structure memory devices can be utilized in the synthesis of charge trapping layers composed of gold nanoparticles. Kolliopoulou et al reported on the use of silicon-oninsulator (SOI) wafers as the substrates and surface modified colloidal gold nanoparticles adsorbed on the APTES-coated tunnelling oxide layers [50]. After the fabrication of source-drain junctions and gateelectrode definition, MOSFET-structure memory devices were fabricated.…”
Section: Mos Field-effect Transistor-type Memory Devicesmentioning
confidence: 99%
“…Inorganic species used in these memories include semiconductor nanoparticles (ZnO, CdSe, Si, CuO and so on) and metal nanoparticles (Au, Ag, FeNi and so on). [22][23][24][25][26][27][28] Both insulating polymers, such as polyimide (PI), poly(methylmethacrylate) and polystyrene, and conducting polymers, such as poly(Nvinylcarbazole) and poly(2-methoxy-5-(2-ethyhexoxy)-1,4-phenylene …”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%